Abby Yadi: From fish to business - Sophie Kuasi (Asia Pacific Network, 2019)
Abby Yadi once had his name written on a bullet after taking an inside photograph of a Defence Force helicopter which was published on the front page of the Post-Courier. His family was also threatened during the Bougainville Crisis.